PELATIHAN PEMBUKUAN KEUANGAN DAN PEMASARAN ONLINE BAGI PENGRAJIN DAUN LONTAR DI DESA TINDANG, KABUPATEN GOWA, SULAWESI SELATAN - haerana, haerana; Abdi, Abdi; Burhanuddin, Burhanuddin (Jurnal Pengabdian Masyarakat Multidisiplin, 2023)
Palm leaf craft is a small business craft made from palm leaves and the frame of the craft is made of bamboo. This craft is manifested in the form of a cake/food cover which is often called "Bosara", which is a special food/cake cover for traditional events or government activities. The existence of Lontar leaf handicrafts in Tindang Village is the result of the creativity of residents who take advantage of the many Lontar trees that grow in the Village, there are many craftsmen in Tindang Village but the partners in this PKM are the "seruni" craftsmen group and the "tulip" craftsmen group, the activities will be held on 15-16 November 2022. This craft business is still managed very simply due to limited capital and is only produced if someone orders it. Therefore this PKM aims to: 1) increase partners' understanding of financial accounting; 2) improve the ability of partners in online marketing. The program implementation methods carried out are: (1) Financial bookkeeping training; (2) marketing training; and (3) assistance. The results of the evaluation of PKM activities show that 95% of participants have experienced increased knowledge about business management and 95% of participants have increased their skills in making websites as a means of online marketing.